Sistemas de culturas sob diferentes manejos por longa duração alteram as formas de fósforo do solo? - Casali, Carlos Alberto (2012)
The thesis objective was to evaluate the forms of accumulation and release of phosphorus from cover crops waste under long time of different soil management systems and its relationship with the soil phosphorus forms. The experiment was established in 1986 on an Oxisol in the IAPAR experimental station in Pato Branco, Paraná State, Brazil. The treatments consisted of six winter cover crops (blue lupine, vetch, oats, radish, rye and wheat) and the winter fallow treatment, cultivated under no-tillage (NT) and conventional (CT). In September 2011 were collected soil samples (0-5 and 5-10 cm) and the shoots of winter cover crops. Confected litterbags (0.2 x 0.2 m) were collected at 7, 14, 28, 56 and 112 days after the cover crops management. In the residues collected, we assessed the accumulation of C, N, P, and held the fractionation of P. In the soil samples, we made the separation of aggregates by wet way and in the original soil and aggregates we evaluated the content of total C, N, P, the P forms, and the acid phosphatase activity. The distribution of P forms in the cover crops tissue varies among species and their accumulation was a function of nutrient soil P availability, as in NT. But for all of them, the soluble inorganic P was the principal storage form. The release of P from plant residues depends not only on its rate of decomposition, but also on the content of total and soluble P. The vetch and rye have great potential to recycle soil P, and this amount of P should be considered when prescribing phosphorus fertilization for the culture implanted in sequence. However, the long term cultivation of different winter cover crops did not affected the soil P forms in highly weathered clay soils, managed under NT and CT. On the other hand, practices that favor the accumulation of organic residues on the soil surface as the NT system, increase the acid phosphatase enzyme activity and labile organic and inorganic P forms, besides the formation of larger aggregates, which have higher levels of C, N, total P and organic labile P.